Animal Activities of the Key Herbivore Plateau Pika (Ochotona curzoniae) on the Qinghai-Tibetan Plateau Affect Grassland Microbial Networks and Ecosystem Functions - Jiawei Yang; Sijie Wang; Wanghong Su; Qiaoling Yu; Xiaochen Wang; Qian Han; Yuting Zheng; Jiapeng Qu; Jiapeng Qu; Xiangzhen Li; Huan Li; Huan Li; et al. (Frontiers in Microbiology, 2022)
Plateau pikas (Ochotona curzoniae) are high-altitude model animals and famous “ecosystem engineers” on the Qinghai-Tibet Plateau. Pika activities may accelerate the degradation of alpine meadows. Nevertheless, little is known about the responses of bacterial, fungal, and archaeal communities, and ecosystem multifunctionality to pika perturbations. To address this question, we studied the impacts of only pika disturbance and combined disturbance (pika disturbance and grazing) on ecological networks of soil microbial communities and ecosystem multifunctionality. Our results demonstrated that Proteobacteria, Ascomycota, and Crenarchaeota were dominant in bacteria, fungi, and archaea, respectively. Bacteria, fungi, and archaea were all influenced by the combined disturbance of grazing and pika. Most fungal communities became convergent, while bacterial and archaeal communities became differentiated during the succession of surface types. In particular, the bacterial and fungal networks were less stable than archaeal networks. In response to the interference, cross-domain cooperation between bacterial and fungal communities increased, while competitive interactions between bacterial and archaeal communities increased. Pika disturbance at high intensity significantly reduced the ecosystem multifunctionality. However, the mixed effects of grazing and pika weakened such influences. This study revealed how pika activities affected microbial networks and ecosystem multifunctionality. These results provide insights to designing reasonable ecological management strategies for alpine grassland ecosystems.